2014
DOI: 10.1007/s00203-014-0980-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Microcystis cyanophages in two different freshwater environments

Abstract: Bacteriophages rapidly diversify their genes through co-evolution with their hosts. We hypothesize that gene diversification of phages leads to locality in phages genome. To test this hypothesis, we investigated the genetic diversity and composition of Microcystis cyanophages using 104 sequences of Ma-LMM01-type cyanophages from two geographically distant sampling sites. The intergenetic region between the ribonucleotide reductase genes nrdA and nrdB was used as the genetic marker. This region contains the hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Following the identification of NblA as a pivotal component of PBS degradation in S. elongatus , involvement of NblA in the decomposition of PBSs in a red alga (Kawakami et al, 2009) and in diverse cyanobacteria was reported (reviewed in Schwarz and Forchhammer, 2005). Interestingly, genes encoding NblA homologues were also identified in cyanophages, supporting the hypothesis that PBS degradation driven by phage-encoded NblA provides nutrients and is thus advantageous for the phage lifecycle (Yoshida et al, 2008;Gao et al, 2012;Yoshida-Takashima et al, 2012;Nakamura et al, 2014;Ou et al, 2015;Voorhies et al, 2016).…”
Section: Pbs Disassembly and Degradationmentioning
confidence: 86%
“…Following the identification of NblA as a pivotal component of PBS degradation in S. elongatus , involvement of NblA in the decomposition of PBSs in a red alga (Kawakami et al, 2009) and in diverse cyanobacteria was reported (reviewed in Schwarz and Forchhammer, 2005). Interestingly, genes encoding NblA homologues were also identified in cyanophages, supporting the hypothesis that PBS degradation driven by phage-encoded NblA provides nutrients and is thus advantageous for the phage lifecycle (Yoshida et al, 2008;Gao et al, 2012;Yoshida-Takashima et al, 2012;Nakamura et al, 2014;Ou et al, 2015;Voorhies et al, 2016).…”
Section: Pbs Disassembly and Degradationmentioning
confidence: 86%
“…Additionally, the interaction of NblA with phycobilisomes attached to thylakoid membranes supports a role for NblA in the sequential disassembly of this large pigment complex (Sendersky et al ., , ). Genes encoding homologues of NblA were identified in several cyanophages – a finding suggesting that stimulation of phycobilisome degradation during infection is beneficial for the phage lifecycle (Yoshida et al ., ; Gao et al ., ; Yoshida‐Takashima et al ., ; Nakamura et al ., ; Ou et al ., ; Voorhies et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Molecular genomic analysis of this strain led to the identification of the g91 gene, which was characterized as a viral sheath protein-encoding gene [12,13,19,26,33,34].…”
Section: Introductionmentioning
confidence: 99%